Commercial Communication in the Digital Age Information or Disinformation? - Siegert, Gabriele (De Gruyter Mouton, 2017)
In today's digital age, online and mobile advertising are of growing importance, with advertising no longer bound to the traditional media industry. Although the advertising industry still has broader access to the different measures and channels, users and consumers today have more possibilities to publish, get informed or communicate - to "co-create" -, and to reach a bigger audience. There is a good chance thus that users and consumers are better informed about the objectives and persuasive tricks of the advertising industry than ever before. At the same time, advertisers can inform about products and services without the limitations of time and place faced by traditional mass media. But will there really be a time when advertisers and consumers have equal power, or does tracking users online and offline lead to a situation where advertisers have more information about the consumers than ever before? The volume discusses these questions and related issues.